STUDIES ON GONOCOCCUS INFECTION : I. PILI AND ZONES OF ADHESION: THEIR RELATION TO GONOCOCCAL GROWTH PATTERNS - Swanson, John (The Rockefeller University Press, 1971)
The four colony types of several different strains of gonococci were isolated by selective transfers on agar. These colony variants differed in the degree of autoagglutination which occurred when they were grown in fluid medium. It was found that this clumping behavior was related to the colonial type, with type 2 isolates exhibiting the greatest autoagglutination followed by types 3, 1, and 4. Electron microscopic examination of thin sections indicated that the clumping in fluid medium was mediated by peculiar zones of adherence of the outer membranes of gonococci. These resembled the gap junctions seen in animal cell systems but differed in that the gonococcal membranes involved in the zone of adherence did not bear typical surface modifications. Electron microscopic study of negatively stained specimens of gonococci revealed that pili with a diameter of approximately 85 A and a length up to 4 µ were present on the surfaces of all type 1 and type 2 gonococci examined, and were not seen on any type 3 or 4 gonococci. The consistent presence of pili on type 1 and type 2 gonococci which are virulent colony forms and the lack of pili on avirulent colony types 3 and 4 suggests a relationship between the gonococcal pili and pathogenetic potential of the organisms.